(9n2 - 121) = (3n + 11) (3n - 11)
3n(n+1] + 5 is the nth term
5
The Series has the formula 3n + 1/2(n - 1)(n - 2) = 3n + 1/2(n2 - 3n + 2) which simplifies to, 1/2(n2 +3n + 2)
3n and n = 4? 3n ( the four replaces the n 3(4) = 12 =======
3n^4 divided by 3n^3 = n
When n=30, 3n-1 = 89 .
Just plug in 30 for n in 3n-1. The answer is 89.
(9n2 - 121) = (3n + 11) (3n - 11)
3n(n+1] + 5 is the nth term
t(n) = 28-3n where n = 1,2,3,...
5
The Series has the formula 3n + 1/2(n - 1)(n - 2) = 3n + 1/2(n2 - 3n + 2) which simplifies to, 1/2(n2 +3n + 2)
The nth term of this sequence is 3n + 4
t(n) = 3n2 + n = n(3n + 1)
The nth term of the sequence 3n + 4 can be calculated by substituting the value of n into the formula. For example, if n = 1, the first term would be 3(1) + 4 = 7. If n = 2, the second term would be 3(2) + 4 = 10. Therefore, the nth term of the sequence is 3n + 4.
Well, isn't that a happy little equation we have here! To solve 3n - 2n, all you need to do is subtract 2n from 3n, which leaves you with n. So, the answer is simply n, a beautiful and peaceful solution. Just like painting a serene landscape, sometimes the simplest answers can bring the most joy.